Interação dinâmica de aerogeradores de indução DFIG e FSIG conectados em um mesmo alimentador de distribuição - Rhode, Thiago (2019)
The demand for electric energy by the current society associated with the need of socioenvironmental impacts mitigation caused by the extraction and transport of this energy is a challenge to the electricity section agents. In this regard, the wind energy connected directly to the distributing network presents itself as a suitable solution to this reality and, because of this, it has already been widely developed in several countries. Among the wind turbine technologies with the biggest applicability stands out the systems of fixed speed with squirrel cage induction generator (FSIG) and of variable speed with doubly fed induction generator (DFIG). As a result of the operative requirement level raise, there is a tendency to replace the first deployed wind turbine – FSIG for generators with superior technological levels – DFIG both in the plants already operating as in new wind farms. However, for techno-economic feasibility reasons, the process improvement is gradual. This leads to the occurrence of wind farms of different technologies operating simultaneously in the same grid. Although the individual operation of these wind turbines is already known, there is a need to identify the impacts of its parallel operation. In this context, this work seeks to identify and evaluate the dynamic interaction of DFIG and FSIG induction generators connected to the same system distribution feeder under different operating conditions and generator arrangements. To this end, it has been implemented a test system in which generators of two technologies connected. In this system, several factors were varied, such as, insertion levels of the wind turbines, feeder loading and electric fault position and, for these conditions the influence of an FSIG wind farm on the dynamic behavior of the DFIG wind turbines was evaluated. The obtained results show that the existence of FSIG plants significantly influences the behavior of the DFIG aerogenerator, mainly in the reestablishment of the terminal voltage and the deviation of the angular velocity of the wind turbine in the post-fault period.